Coping strategies tailored to the management of fear of recurrence and adaptation for E‐health delivery: The FoRtitude intervention. Issue 6 (16th February 2017) - Wagner, Lynne I.; Duffecy, Jenna; Penedo, Frank; Mohr, David C.; Cella, David
Abstract : Fear of recurrence has been well documented among cancer survivors, yet there have been few publications on strategies for coping with this fear. This report describes 3 coping strategies tailored to the management of fear of recurrence and the delivery of these coping strategies through FoRtitude, a targeted e‐health intervention designed to teach breast cancer survivors coping strategies targeted at fear of recurrence with a Web‐ and text messaging–based approach.